Hubungan Antara Gaya Belajar, Kemandirian Belajar dan Minat Belajar dengan Hasil Belajar Biologi di SMA Negeri 5 Palu - Qadriah, Nur; Astija, Astija; Buntu, Amalia; Alibasyah, Lestari M.P.; Dhafir, Fatma; Agni, Raya (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to examine the relationship between learning styles, learning independence, and learning interest with biology learning outcomes among Grade X students at SMA Negeri 5 Palu. This research used a quantitative approach with a correlational method. A total of 176 students were selected using proportional random sampling. The instruments used were questionnaires and documentation of biology scores. Data analysis involved validity tests, reliability tests, normality tests, Pearson correlation, and multiple linear regression. The results showed a significant relationship between learning style (r = 0.668), learning independence (r = 0.747), and learning interest (r = 0.732) with biology learning outcomes (p < 0.05). Multiple regression analysis revealed that the three variables simultaneously influenced learning outcomes, with the regression equation Y = 9.771 + 0.502Xâ‚ + 0.314Xâ‚‚ + 0.357Xâ‚ƒ and RÂ² = 0.656. This indicates that the three independent variables contribute 65.6% to the variance in biology learning outcomes. The findings highlight the importance of internal student characteristics in academic achievement, especially in biology learning.